Differential Role for Activating FcγRIII in Neointima Formation After Arterial Injury and Diet-Induced Chronic Atherosclerosis in Apolipoprotein E-Deficient Mice - Asare, Yaw; Koehncke, Janine; Selle, Jaco; Simsekyilmaz, Sakine; Jankowski, Joachim; Shagdarsuren, Gansuvd; Gessner, Johannes E.; Bernhagen, Jürgen; Shagdarsuren, Erdenechimeg (Frontiers in Physiology, 2020)
Atherogenesis and arterial remodeling following mechanical injury are driven by inflammation and mononuclear cell infiltration. The binding of immune complexes to immunoglobulin (Ig)-Fc gamma receptors (FcγRs) on most innate and adaptive immune cells induces a variety of inflammatory responses that promote atherogenesis. Here, we studied the role of FcγRIII in neointima formation after arterial injury in atherosclerosis-prone mice and compared the out-come and mechanism to that of FcγRIII in diet-induced ‘chronic’ athero¬sclerosis. FcγrIII–/–/Apoe–/– and control Apoe–/– mice were subjected to wire-induced endothelial denudation of the carotid artery while on high-fat diet (HFD). FcγrIII deficiency mitigated neointimal plaque formation and lesional macrophage accumulation, and enhanced neointimal vascular smooth muscle cell (VSMC) numbers. This went along with a reduced expression of tumor necrosis factor-alpha (TNF-alpha), monocyte chemoattractant protein-1 (MCP-1/CCL2), and vascular cell adhesion molecule-1 (VCAM-1) in the neointimal lesions. Interestingly, in a chronic model of diet-induced atherosclerosis, we unraveled a dichotomic role of FcγRIII in an early versus advanced stage of the disease. While FcγrIII deficiency conferred atheroprotection in the early stage, it promoted atherosclerosis in advanced stages. To this end, FcγrIII deficiency attenuated pro-inflammatory responses in early atherosclerosis but promoted these events in advanced stages. Analysis of the mechanism(s) underlying the athero-promoting effect of FcγrIII deficiency in late-stage atherosclerosis revealed increased serum levels of anti-oxidized-LDL immunoglobulins IgG2c and IgG2b. This was paralleled by enhanced lesional accumulation of IgGs without affecting levels of complement-activated products C5a or C5ar1, FcγRII, and FcγRIV. Moreover, FcγrIII-deficient macrophages expressed more FcγrII, Tnf-alpha, and Il-1beta mRNA when exposed to IgG1 or oxLDL-IgG1 immune complexes in vitro, and peripheral CD4+ and CD8+ T-cell levels were altered. Collectively, our data suggest that deficiency of activating FcγRIII limits neointima formation after arterial injury in athero-sclerosis-prone mice as well as early-stage chronic atherosclerosis, but augments late-stage atherosclerosis suggesting a dual role of FcγRIII in atherogenic inflammation.